DETERMINATION OF URBAN SPRAWL AND TRANSFORMATION PROCESS: THE CASE OF DİYARBAKIR - Dağlı, Dündar; Çağlıyan, Ayşe (Marmara Üniversitesi, 2021)
This study, which examines the urban sprawl process of an ancient city, Diyarbakır, aims to determine the process of change and transformation of the city on a temporal and spatial scale. The urbanization process in Diyarbakır has been examined under two headings: pre-Republican and Republican period. The urban sprawl of Suriçi in the pre-Republican period was investigated using historical data and academic studies. Orthophotos were used as the main source of data in determining urban sprawl in the Republican period. By overlapping orthophotos with the current housing base maps, the temporal and spatial expansion of the city has been revealed more accurately. The research findings show that the urbanization process has accelerated since the second half of the 20th century and the largest spatial increase was observed in the last quarter of the same century. Since the 2000s, the process of change and transformation has accelerated both horizontally and vertically. As a result, the city which consisted only of Suriçi in the 1930s has experienced a 10-fold growth in residential areas until today. The analyses indicate that the direction of urban sprawl was on West-Northwest axis in almost all periods. As it is the case today, it is estimated that in the future the city will continue its sprawl on Elazığ Street and Şanlıurfa Boulevard and in the immediate vicinity.

Kadim bir kent olan Diyarbakır’ın mekânsal gelişiminin incelendiği bu araştırmada kentin zamansal ve mekânsal ölçekte gelişim ve dönüşüm sürecinin belirlenmesi amaçlanmıştır. Diyarbakır’da kentleşme süreci, Cumhuriyet öncesi ve Cumhuriyet Dönemi olmak üzere iki başlıkta incelenmiştir. Cumhuriyet öncesi dönemde, Suriçi’nin mekânsal gelişimi tarihi veriler ile akademik çalışmalardan faydalanılarak oluşturulmuştur. Cumhuriyet Dönemi’nin mekânsal gelişiminin belirlenmesinde ise temel veri kaynağı olarak ortofotolar kullanılmıştır. Ortofotoların güncel hâlihazır konut verileri ile örtüştürülmesiyle kentin zamansal ve mekânsal gelişimi daha doğru bir şekilde ortaya konulmaya çalışılmıştır. Araştırma bulguları, 20. yüzyılın ikinci yarısından itibaren kentleşme sürecinin hızlandığını ve aynı yüzyılın son çeyreğinde en büyük alansal artışın yaşandığını göstermektedir. 2000’li yıllardan itibaren ise hem yatayda hem de dikeyde gelişim ve dönüşüm süreci hızlanmıştır. Sonuç olarak, 1930’larda Suriçi’nden ibaret olan kent, günümüze kadar konut alanlarında 10 kat büyüme yaşamıştır. Analiz sonuçları, kentsel gelişim yönünün neredeyse bütün dönemlerde batı-kuzeybatı eksenli olduğunu göstermiştir. Günümüzde olduğu gibi gelecekte de, kentin Elazığ Caddesi ile Şanlıurfa Bulvarı üzerinde ve yakın çevresinde gelişimini sürdüreceği tahmin edilmektedir.
KENTSEL GELİŞİM VE DÖNÜŞÜM SÜRECİNİN BELİRLENMESİ: DİYARBAKIR ÖRNEĞİ
Keywords: Human Geography; Beşeri Coğrafya